(untitled) (Bangladesh Journal of Zoology, 2015)
Activity pattern of white-breasted waterhen (Amaurornis phoenicurus) was studied during May 2007 to April 2008 at Jahangirnagar University Campus, Savar, Dhaka, Bangladesh. They spent most of the daily time (35.46%) for foraging and feeding. Hiding was the second highest activity (26.75%) while moving, preening, calling, resting activities and changing other wetland birds constituted 11.33%, 8.59%, 6.13%, 5.20% and 5.12%, respectively. Breeding season lasted from February to July with the breeding activities found in April (9.41%). The white-breasted waterhens avoided the conflict with other wetland birds by hiding themselves. Bangladesh J. Zool. 41(2): 189-198, 2013